Requirement Model for UUM Mobile Course Evaluation System - Nisofia, Nilaeh (2009)
Today people can access information without need for such efforts. Mobile technologies are rapidly growing and can assist in making this a reality. This study uses the mobile application to provide an alternative of a new method that utilizes mobile technology for course evaluation system. The aims of this study are to identify the requirement and develop the prototype Mobile Course Evaluation System. This system is alternative way in facilities and more convenience for student to evaluate of their courses. Moreover, the purpose of this study is to evaluate system prototype that using usability evaluation to get user's satisfaction by students. The study followed the phases in the Increment Iterative extreme Programming (IIXP) methodology. The findings of this study are requirement model, the prototype Mobile Course Evaluation System and user satisfaction results indicate that the most of students agree with using this system in terms of usefulness, ease of use and outcome future use of the system. This finding will be encouragement to improve and enhance into the existing system.